(untitled) (Economic and Political Thought, 2022)
Macroeconomic stability should be defined as price stability, full employment, positive long-term growth over the long term and sound public finances. Maintaining macroeconomic stability is necessary for the smooth process of economic development. For years, there has been discussion in mainstream economics about the best ways to achieve this goal. The article presents the main theoretical assumptions on which the discussion is based and tries to verify the assumptions of the models with the economic reality.